A mutant dec-1 transgene induces dominant female sterility in Drosophila melanogaster. - Spangenberg, D.K.; Waring, G.L. (Genetics, 2007)
The Drosophila dec-1 gene produces three proproteins required for female fertility and eggshell assembly. The three proproteins are distinguished by their C termini. Fc106, the most abundant proprotein, is cleaved within the vitelline membrane to three mature derivatives in a developmentally regulated manner. To define sequences within fc106 that are critical for its function, we created wild-type and mutant versions of an fc106 cDNA transgene. The functional consequences of the mutations were assessed in dec-14, a female-sterile splicing mutant that does not produce the fc106 isoform. The fertility of dec-14 females was restored by the introduction of either a wild-type transgene or a transgene bearing a C-terminal deletion that included fc106-specific sequences. Surprisingly, the removal of internal coding sequences created an aberrant DEC-1 proprotein that induced female sterility when introduced into wild-type flies. Dominant female sterility was not associated with larger deletions that included the fc106 N terminus, suggesting that abnormal juxtaposition of N- and C-terminal sequences in the aberrant proprotein interfered with endogenous DEC-1 proteins. Changes in the fractionation behavior of the endogenous fc106 C-terminal derivative, s60, and morphological changes in the endochorion in response to expression of the aberrant proprotein support this interpretation.